APLIKASI ANALISIS FAKTOR KONFIRMATORI UNTUK MENGETAHUI HUBUNGAN PEUBAH INDIKATOR DENGAN PEUBAH LATEN YANG MEMPENGARUHI PRESTASI MAHASISWA DI JURUSAN MATEMATIKA FMIPA UNSRI - Sri Indra Maiyanti; Oki Dwipurwani; Anita Desiani; Betty Aprianah (Jurnal Pendidikan Matematika, 2008)
To know the correlation between indicator variables and latent variables that the influence students’ achieviement in majors of mathematics of FMIPA UNSRI used Confirmatory Factor Analysis by maximum likelihood method to estimate the model parameters. Confirmatory Factor Analysis is one of the methods of multivariate analysis used to confirm whether or not the model that is build is match the hypothesis.  The result of tained that the latent variable of has a background of family could be measured by indicator variables of father’s education (x1), mother’s education (x2) and parent’s income (x3), where indicator variables that give great contribution is mother’s education is 0.84.  The latent variables of learning environment of campus (ξ2) could be measured by indicator variables of time using far house to campus (x4), learning facilities at home (x5) and learning concentration (x8), where indicator variables that give great contribution is learning facilities at home is 0.80.  The latent variables of attitude toward almamater (ξ3) could be measured by indicator variables of classroom facilities in major (x11), library facilities (x12) and computer facilities (x13), where indicator variables that give great contribution is classroom facilities in major is 1.08.  The latent variable of perseption toward lecturers (ξ4) could be measured by indicator of evaluation system given by lecturer (x16), learning system given by lecturer (x17), assigment system given by the lecturer (x18), and the relationship with academic advisor (x19), where indicator variables that give great contribution is learning system is 0.73.